PENGARUH KUALITAS PELAYANAN KARYAWAN TERHADAP KEPUASAN TAMU DI EDOTEL BUNDO KANDUNG SMK N 9 PADANG - Lismarni, Lismarni; Chair, Ira Meirina; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2017)
The purpose of this research is to find the effect of employee service quality (X) on guest satisfaction(Y) in Edotel Bundo Kandung SMK N 9 Padang. This Research is classified as quantitative research. The population of this research are all quest that stayed at Edotel Bundo Kandung SMK N 9 Padang at period of 2013 until 2015. This research use non-probability sampling as the sampling method, it means that this sampling method will not give the same exact change for each population to be selected as research sample. This research used incidental sample. That means all population that met the researcher during data gathering process will be selected as the data source or sample. Total sample that used in this research are 100 samples. The data are collected by spreading research questionnaire items are constructed by using Likert scale and the validity and reliability of each questionnaire have been tasted. The result of this research shown that on employee service quality each good and fair category(48%), the level of quest satisfaction level are on good category (55%). This means that employee service quality have positive and signifiant effects on quest satisfaction in Edotel Bundo Kandung SMK N 9 PadangKeywords: employee service quality, quest satisfaction